Primary aortoduodenal fistula and chronic Q fever infection. Issue 2 (4th February 2021) - Do, Cuong Nghi; Mar, Ethan Oskar; Sim, Beatrice; Looke, David
Abstract : We report a case of chronic Q fever presenting with catastrophic bleeding from an infected abdominal aortic aneurysm causing a primary aortoduodenal fistula in an 80-year-old retired farmer. This presentation is rarely reported in literature and only through case reports. Early diagnosis and definitive surgery were critical to a successful outcome. Serological diagnosis of Q fever was initiated on the patient's past exposure to animal reservoirs. Complicating the case was ongoing gastrointestinal bleeding postsurgery, with multiple endoscopies undertaken before a culprit remnant fistula was found. This case highlights the value in considering Coxiella burnetii as an underlying cause in patients with known risk factors presenting with primary aortoduodenal fistulas. Though rare, it represents a readily treatable cause.